Gendering Nationalism Intersections of Nation, Gender and Sexuality (Springer International Publishing, 2018)
This volume offers an empirically rich, theoretically informed study of the shifting intersections of nation/alism, gender and sexuality. Challenging a scholarly legacy that has overly focused on the masculinist character of nationalism, it pays particular attention to the people and issues less commonly considered in the context of nationalist projects, namely women and sexual minorities. Bringing together both established and emerging researchers from across the globe, this multidisciplinary and comparison-rich volume provides a multi-sited exploration of the shifting contours of belonging and Otherness generated by multifarious nationalisms. The diverse, and context specific positionings of men and women, masculinities and femininities, and hegemonic and non-normative sexualities, vis-à-vis nation/alism, are illuminated through a vibrant array of contemporary theoretical lenses. These include historical and feminist institutionalism, post-colonial theory, critical race approaches, transnational and migration theory and semiotics.